Ancient environmental genome reveals a migratory brown bear individual in Early Holocene Scandinavia - Ernst Johnson; Isabelle Sofie Feinauer; Carl Regnéll; Chenyu Jin; J. Camilo Chacón-Duque; Gonzalo Oteo-García; Richard Gyllencreutz; Sarah L. Greenwood; Love Dalén; Peter D. Heintzman; Anna Linderholm (Proceedings of the National Academy of Sciences, 2026)
After the last ice age, species migrated into a newly deglaciated Scandinavia. Brown bear recolonization is thought to have occurred from two directions—from the south and the northeast—resulting in a nonoverlapping distribution of two distinct mitochondrial clades. A contact zone in central Sweden separates populations with mitochondrial clade 1a in the south from those with clade 3a in the north. However, a paucity of brown bear subfossils in Scandinavia has limited testing of this prevailing model using ancient DNA. Here, we present a high-coverage brown bear mitogenome (231×) and nuclear genome-wide data (0.05×) extracted from lake sediment dated to 9.6 cal. ka BP from northern Sweden, representing the oldest known record of brown bear in the region. At this point in the Early Holocene, the Fennoscandian Ice Sheet was in its final stages of recession. Surprisingly, our analyses suggest that this environmental genome represents one male individual carrying clade 1a and with southern brown bear nuclear ancestry, despite being found far north of the contact zone. This suggests the individual was a migratory bear and had dispersed northward from its birthplace. Our finding adds to the scarce genomic record of Early Holocene brown bears and highlights the use of sedimentary ancient DNA as a powerful source of genomic information.